Education sector risk assessment in the time of pandemic - Hasmin T. Ignacio; Jennifer P. Alinsunod; Heronafine C. De Guzman; Francisco D. Esponilla II (Institute of Advanced Engineering and Science, 2022)
The study explored school teachers, school administrators, and staff exposure to the COVID-19 virus in the workplace, the risk reduction practices of their organizations, organization response to those workers who were found positive of Coronavirus, and lastly the respondents’ suggestions to help their organization protect their employees. The study used a researcher-made risk assessment questionnaire, through Google Forms. The questionnaire was used in 25 selected respondent schools in the Philippines. The study revealed that the majority of the respondents were adopting the work from home, the rest of the respondents are reporting to school 1 up to 6 days a week. There are three major categories in handling the COVID-19 positive person such as implementation of health protocols, support to dimension of wellness, quick and immediate response. Moreover, the top three suggestions of the respondents are: i) Embrace new normal (appointments, enrolment, admission, and other transactions should be online); ii) Regularly provide vitamins, health kits, face masks, face shields, alcohol, and other medical supplies; iii) Provide training and webinars on health, safety training, mental health awareness, and online teaching.